Effect of Pre-Eclampsia on plasma and erythrocytic divalent cation concentrations and their Bioenergetics of Transport - Igwe, C. U.; Okafor, P. A.; Ibegbulem, C. O.; Okwara, J. E. (Asian Journal of Medical Sciences, 2014)
Background: Pre-eclampsia is a syndrome of pregnancy-induced hypertension with proteinuria, which has high prevalence rate among blacks. Aims and Objectives:To study the effect of pre-eclampsia on bioenergetics for the transport of erythrocytic cations to plasma, the plasma and erythrocytic levels of magnesium (Mg), calcium (Ca), copper (Cu), zinc (Zn), manganese (Mn) and selenium (Se) were measured by atomic absorption spectrophotometry in 100 pre-eclamptic women matched for gestation age with 100 normal pregnant subjects. These were also age-matched with 100 non-pregnant women. Results: The plasma and erythrocytic levels of the minerals were significantly (p < 0.05) lower in the pre-eclamptic patients than the healthy pregnant and the non-pregnant women. Although, levels of these minerals were also reduced in the healthy pregnant women relative to the non-pregnant subjects, only the plasma and erythrocytic levels of Ca, Cu, Mn and Se showed significant (p < 0.05) depreciations. Pre-eclampsia and pregnancy did not affect significantly (p > 0.05) the divalent-cation-based erythrocytic membrane free energy. Conclusion: Our results suggest that low levels of these minerals, especially Mg and Ca in pre-eclampsia, may have roles to play in the development of hypertension in these patients, and calls for intensified research into mineral supplementation as a key for possible prevention or management of pre-eclampsia. DOI: http://dx.doi.org/10.3126/ajms.v6i2.11109 Asian Journal of Medical Sciences Vol.6(2) 2015 19-24